2012
DOI: 10.1186/2191-219x-2-12
|View full text |Cite
|
Sign up to set email alerts
|

[11C]Flumazenil brain uptake is influenced by the blood-brain barrier efflux transporter P-glycoprotein

Abstract: Background[11C]Flumazenil and positron emission tomography (PET) are used clinically to assess gamma-aminobutyric acid (GABA)-ergic function and to localize epileptic foci prior to resective surgery. Enhanced P-glycoprotein (P-gp) activity has been reported in epilepsy and this may confound interpretation of clinical scans if [11C]flumazenil is a P-gp substrate. The purpose of this study was to investigate whether [11C]flumazenil is a P-gp substrate.Methods[11C]Flumazenil PET scans were performed in wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The study by Bankstahl et al 39 did show that the regional differences and the differences between controls and epileptic rats became somewhat more pronounced when P-gp was inhibited by a low dose of tariquidar. [ 11 C]Flumazenil, a GABA A receptor antagonist and a moderate P-gp substrate, 66 has been used to study differences between epileptic and control rats with respect to both BBB pharmacokinetics and receptor binding. 101 This study did not indicate changes at the level of BBB but rather indicated that the differences observed between the two groups were caused by changes at the GABA A receptor level.…”
Section: ■ Pet P-gp Tracersmentioning
confidence: 99%
“…The study by Bankstahl et al 39 did show that the regional differences and the differences between controls and epileptic rats became somewhat more pronounced when P-gp was inhibited by a low dose of tariquidar. [ 11 C]Flumazenil, a GABA A receptor antagonist and a moderate P-gp substrate, 66 has been used to study differences between epileptic and control rats with respect to both BBB pharmacokinetics and receptor binding. 101 This study did not indicate changes at the level of BBB but rather indicated that the differences observed between the two groups were caused by changes at the GABA A receptor level.…”
Section: ■ Pet P-gp Tracersmentioning
confidence: 99%
“…1,2 Recent ex vivo and in vivo data, however, suggest that [ 11 C]flumazenil is a P-gp substrate in rodents. 35 It has been hypothesized that P-glycoprotein (P-gp) is upregulated in areas with epileptic activity. 6 If [ 11 C]flumazenil is indeed a P-gp substrate in humans, upregulation of P-gp at the blood–brain barrier (BBB) due to epilepsy could lead to reduced cerebral uptake of [ 11 C]flumazenil, and thus to erroneous interpretation of GABA A receptor density changes.…”
Section: Introductionmentioning
confidence: 99%
“…However, differences in metabolite rates could affect the radioactive concentration in blood and therefore is a potential bias on the V T * calculations. The heart ventricle image-derived input function serves for calculation of distribution volume for tracers without substantial binding in the myocardium and without important metabolism during the scan [48, 49]. Finally, we calculated V T * on a group basis rather than for individual mice, thus affording a better comparison of PET scans and the ex vivo experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the V T * index is a less biased measurement than %ID/g in this regard, as it is a steady-state index. Furthermore, [ 18 F]flumazenil is a substrate of the blood-brain barrier efflux transporter P-glycoprotein [49], we cannot rule out that anesthetics might have an actions on P-glycoprotein function, further studies in P-glycoprotein knockout animals would be needed.…”
Section: Discussionmentioning
confidence: 99%